Optimal Portfolio Analysis of Private Pension Fund Investment in Indonesia: Markowitz Theory Approach (Efficient Frontier) and Single Index Model Theory - Fardi, Fardi (Dhana, 2025)
This study aims to determine the behavioral characteristics of private pension fund management institutions in Indonesia in making investment decisions in terms of risk aspects. In addition, this study also wants to test whether the current investment income is optimal and test whether there are differences in income levels from the three types of pension fund programs in Indonesia. The data used in this study are secondary data obtained from the Financial Services Authority (OJK). The data analysis techniques used are using the weighted average of investment risk, the application of Markowitz (Efficient Frontier) theory and SIM, especially the Treynor ratio, and non-parametric difference testing with the Mann-Whitney U Test and the Kruskal Wallis Test. The results of this study indicate that: First, the behavioral characteristics of investment decision-making of pension fund management institutions tend to avoid risk. Second, for the PPMP and PPIP pension fund programs, the optimal portfolio composition is 50% stocks with actual returns and 50% stocks with returns that take into account SIM, while for DPLK the optimal composition is 40% stocks with actual returns and 60% stocks with returns that take into account SIM. Third, in aggregate and individually for each investment instrument there are differences in returns on the three types of pension fund programs in Indonesia